Preserving digital heritage: At the crossroads of Trust and Linked Open Data. (October 2015) - Solodovnik, Iryna; Budroni, Paolo
Regardless of current or future technologies, accessing digitally preserved information resources will always pose challenges. There is a plethora of models, standards and best practices addressing the different facets for the preservation of digital objects. The management of digital objects requires well-defined policies and data management plans that include all processes within their specific lifecycle. To achieve high levels of data sharing and long-term re-use of data, APARSEN recommends developing an Interoperable Framework for Persistent Identifiers, paving the way for a 'Ring of Trusted Persistent Identifiers for Linked Open Data'. To enable semantic interoperability of such a Ring, this article proposes to map LODE-BD metadata with the Framework's ontology. The Ring can be further enriched with LOD2 Technology Stack to tackle the problem of trustworthiness of linked data lifecycle while addressing the issue of Big Data. To be trusted, digital libraries need to be audited and certified in compliance with the European Framework for Audit and Certification.